2013
DOI: 10.1128/jb.01495-12
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of 7-Dehydrocholesterol Fatal to Helicobacter pylori Is a Novel Role of Cholesterol Glucosylation

Abstract: The glucosylation of free cholesterol (FC) by Helicobacter pylori cells has various biological significances for the survival of this bacterium. H. pylori cells with glucosylated FC are capable of evading host immune systems, such as phagocytosis by macrophages and activation of antigen-specific T cells, and surviving in the gastric mucosal tissues for long periods. An additional role of cholesterol glucosylation in the survival of H. pylori which is distinct from the role of escaping the host immune system, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, the effect of the cholesterol biosynthetic precursor 7-dehydrocholesterol (7DHC) has been studied. It was found to be fatal to H. pylori (49). Glucosylation detoxified 7DHC, as indicated by the observation that mutant H. pylori lacking the ability to glucosylate cholesterol had higher 7DHC susceptibility (49).…”
Section: Effect Of Sterols and Steroids Upon H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of the cholesterol biosynthetic precursor 7-dehydrocholesterol (7DHC) has been studied. It was found to be fatal to H. pylori (49). Glucosylation detoxified 7DHC, as indicated by the observation that mutant H. pylori lacking the ability to glucosylate cholesterol had higher 7DHC susceptibility (49).…”
Section: Effect Of Sterols and Steroids Upon H Pylorimentioning
confidence: 99%
“…It was found to be fatal to H. pylori (49). Glucosylation detoxified 7DHC, as indicated by the observation that mutant H. pylori lacking the ability to glucosylate cholesterol had higher 7DHC susceptibility (49). The effect of other steroids upon H. pylori has also been studied.…”
Section: Effect Of Sterols and Steroids Upon H Pylorimentioning
confidence: 99%
“…Likewise, we have demonstrated that the phosphoramidite chemistry is compatible with biologically relevant functional groups such as olefins and cyclopropanes. In light of the recent discovery that H. pylori enzymes are promiscuous and readily incorporate a variety of cholesterol analogues,16 this modular platform offers accessibility to various phosphatidyl glycolipids to study their biological properties and also to aid in the discovery of new analogues.…”
Section: Methodsmentioning
confidence: 99%
“…The glucosyl-cholesterol complex can be beneficial to H. pylori , because this bacterium can glucosylate toxic sterols and integrate the complex into the membrane without harming the organism. In contrast, mutants of the glucosyl transferase are killed by toxic sterols (159). Cholesterol in H. pylori modifies the membranes so that colonization of the gastric mucosa and expression of Lewis antigen are not impaired (160).…”
Section: Use Of Host Lipids By Extracellular Bacteriamentioning
confidence: 99%